Optimization of Learning in Islamic Religious Education at Miftahul Ulum Vocational School, Tanjung Senang: A Review of the Influence of Problem Based Learning Strategies on Motivation and Learning Outcomes - Titik Wahyuni; Imam Syafe'i; Heni Wulandari (Universitas Muhammadiyah Enrekang, 2024)
This research is motivated by the need for effective learning strategies in increasing student motivation and learning outcomes in Islamic Religious Education (PAI) subjects at Vocational High Schools (SMK). As an integral part of the curriculum, PAI has a central role in shaping students' character, morals and religious values. However, its implementation is often faced with challenges, mainly related to a lack of student involvement and a lack of variety in teaching strategies. Therefore, this research aims to evaluate the effectiveness of implementing the Problem Based Learning (PBL) strategy in increasing student motivation and learning outcomes in PAI subjects at Miftahul Ulum Vocational School, Tanjung Senang. Using a quantitative approach and associative verification method, this research involved class X OTKP and RPL students as research subjects. The research results show that there is a significant relationship between the use of PBL strategies and student learning motivation and learning outcomes, with the PBL variable making a significant contribution in increasing student learning motivation and learning outcomes. The conclusion of this research highlights the importance of implementing innovative learning strategies such as PBL in the context of Islamic religious education in vocational schools, while considering the need for support and attention to challenges that may arise in the implementation process.